2015
DOI: 10.1016/j.vaccine.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Health benefit for the child and promotion of the common good were the two most important reasons for participation in the FinIP vaccine trial

Abstract: Background and aims: The Finnish Invasive Pneumococcal disease (FinIP) vaccine trial was a nationwide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In this study, we analysed data from 5,696 SEED families to explore whether reasons differed by child's diagnostic and behavioural characteristics at enrolment (ie study group). As with other childhood studies, [13][14][15][16][17][18]22,[24][25][26][27][28][29] we found that families participating in this study frequently stated altruism (ie wanting to help other children or families) and perceived personal benefit (ie learning something specific about their child's development) as reasons for participating.…”
Section: Principalfindingssupporting
confidence: 75%
See 4 more Smart Citations
“…In this study, we analysed data from 5,696 SEED families to explore whether reasons differed by child's diagnostic and behavioural characteristics at enrolment (ie study group). As with other childhood studies, [13][14][15][16][17][18]22,[24][25][26][27][28][29] we found that families participating in this study frequently stated altruism (ie wanting to help other children or families) and perceived personal benefit (ie learning something specific about their child's development) as reasons for participating.…”
Section: Principalfindingssupporting
confidence: 75%
“…We established six categories, a priori, based on the existing literature and anecdotal reports from site interviewers: altruism (help others), perceived personal benefit (wants assessment or answers), peripheral relationship with ASD/DD (knows people outside their household with ASD or DD), ASD research interest (stated finding answer/cures/causes of ASD/DD), financial incentive and reputation of agency/investigator (wants to assist, or admires, inviting agency or investigator). [1][2][3][4][5][6][7][8][9][14][15][16][17][18][19][20][21][22][23][24] We added four additional reason categories during the initial coding pass to accommodate the breadth of responses [general research interest (noted research other than ASD/ DD), social encouragement (someone asked or encouraged them to consider the study), desired specific study result (stated a specific outcome of interest) and miscellaneous], resulting in ten final categories plus 'no reason'.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations